Estimation of handgrip position based on force measurement during steady pedaling - Tamura, Y.; Matsushita, K.; Osumi, H. (Journal of Science and Cycling, 2015)
There have been many studies on pedaling skills (Bini et al., 2013) to improve cycling efficiency. Riding position of upper body as well as leg motion is very important for cycling because it has a substantial impact on air resistance and physical fatigue (Burke & Pruitt, 2003). Although camera-based motion capture systems are the most popular solution to measure riders` position during cycling, they limit the range of motion and cannot be applied to actual outdoor cycling.